Microalbuminuria in Metabolic Obesity: A Cross-Sectional Study in a Selected Tertiary Care Hospital of Bangladesh (Journal of Enam Medical College, 2022)
Background: Overweight and obese individuals may have no cardiometabolic risk whereas normal weight individuals may present with cardiometabolic risk. The term‘Metabolic obesity’ has been floated to identify hidden metabolic risks irrespective of BMI. The pathophysiology of metabolic obesity can be explained by microvascular dysfunction and microalbuminuria is a wellknown marker of microvascular dysfunction.Objective: The objective of this study was to find out the association of microalbuminuria with metabolic obesity in Bangladeshi adult subjects.Materials and Methods: This cross- sectional analytical study included 200 individuals who attended outpatient department in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2018 to February 2019. The study subjects were divided into metabolically obese (metabolically unhealthy) group and metabolically non-obese (metabolically healthy) group by metabolic syndrome (MetS) criteria. Metabolic syndrome was defined according to the South Asian Modified-National Cholesterol Education Program (NCEP). Microalbuminuria was defined as a urinary albumin to creatinine of 30 to 300 mg/gm. Demographic profile, BP, height, weight, waist circumference etc. were measured and fasting blood glucose, serum triglyceride, serum HDL-C were estimated and albumin to creatinine ratio (ACR) was calculated. Statistical analysis was done using SPSS version 22.0.Results: The frequencies of metabolically obese (metabolically unhealthy) group and metabolically non-obese (metabolically healthy) group were 128 (64%) and 72 (36%) respectively. Mean values for age (p value 0.001), body mass index (p value 0.027), waist circumference (p